TLR signaling in human antigen-presenting cells regulates MR1-dependent activation of MAIT cells - Ussher, J; van Wilgenburg, B; Hannaway, R; Ruustal, K; Phalora, P; Kurioka, A; Hansen, T; Willberg, C; Phillips, R; Klenerman, P (Wiley, 2016)
Mucosal-associated invariant T (MAIT) cells are an abundant innate-like T lymphocyte population that are enriched in liver and mucosal tissues. They are restricted by MR1, which presents antigens derived from a metabolic precursor of riboflavin synthesis, a pathway present in many microbial species, including commensals. Therefore, MR1-mediated MAIT cell activation must be tightly regulated to prevent inappropriate activation and immunopathology. Using an in vitro model of MR1-mediated activation of primary human MAIT cells, we investigated the mechanisms by which it is regulated. Uptake of intact bacteria by antigen presenting cells (APCs) into acidified endolysosomal compartments was required for efficient MR1-mediated MAIT cell activation, while stimulation with soluble ligand was inefficient. Consistent with this, little MR1 was seen at the surface of human monocytic (THP1) and B-cell lines. Activation with a TLR ligand increased the amount of MR1 at the surface of THP1 but not B-cell lines, suggesting differential regulation in different cell types. APC activation and NF-κB signaling were critical for MR1-mediated MAIT cell activation. In primary cells, however, prolonged TLR signaling led to downregulation of MR1-mediated MAIT cell activation. Overall, MR1-mediated MAIT cell activation is a tightly regulated process, dependent on integration of innate signals by APCs.